DEVELOPMENT AND VALIDATION OF THE METHOD OF VITAMINE E DETERMINATION IN MICROEMULSION COMPOSITIONS BY HIGH-EFFECTIVE LIQUID CHROMATOGRAPHY - S. V. Kursakov; E. G. Kuznetsova; O. M. Kuryleva; L. A. Salomatina; V. I. Sevastianov (Разработка и регистрация лекарственных средств)
The results of development and validation of the method of vitamin E detrmination in microemulsion compositions suitable for its controlling in transdermal delivery systems and also for the incoming control of tocopherol acetate oil solutions presents in the article. The method is based on the vitamin E extraction from the microemulsion by a mixture of acetonitrile - ethyl acetate (80:20) and subsequent analysis by reversed-phase HPLC. The main validation characteristics of the method meet the eligibility criterias. The analytical area of the methodology was from 0.1 to 10.0 mg/g vitamin E concentration. The results of method approbation on transdermal delivery system laboratory samples on microemulsions based are presented.